2021
DOI: 10.1002/for.2763
|View full text |Cite
|
Sign up to set email alerts
|

Do local and global factors impact the emerging markets' sovereign yield curves? Evidence from a data‐rich environment

Abstract: This paper investigates the relation between yield curve and macroeconomic factors for 10 emerging sovereign bond markets using the sample from January 2006 to April 2019. To this end, the diffusion indices obtained under four categories (global variables, inflation, domestic financial variables, and economic activity) are incorporated by estimating dynamic panel data regressions together with the yield curve factors. Besides, in order to capture dynamic interaction between yield curve and macroeconomic/financ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Most of the studies of food waste primarily addressed issues that happened in developed countries (Garnett, 2011; Jörissen et al, 2015; Qian et al, 2020), while much less attention has been given to developing countries or emerging economies, such as China. Benefited from the double‐digit annual high‐speed economic growth since reform and opening‐up policy in the late 1970s, China has become the most important emerging economy in the world (Cepni et al, 2021). In the transition from a developing agricultural country to a developed industrial country and economic development and improvement of people's living standards, Chinese people's attitudes of consumption and behavior patterns have undergone profound changes.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies of food waste primarily addressed issues that happened in developed countries (Garnett, 2011; Jörissen et al, 2015; Qian et al, 2020), while much less attention has been given to developing countries or emerging economies, such as China. Benefited from the double‐digit annual high‐speed economic growth since reform and opening‐up policy in the late 1970s, China has become the most important emerging economy in the world (Cepni et al, 2021). In the transition from a developing agricultural country to a developed industrial country and economic development and improvement of people's living standards, Chinese people's attitudes of consumption and behavior patterns have undergone profound changes.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to previous articles, they argued that the share of international investors may not be directly linked to yields, suggesting the existence of threshold-type or largely country-specific relationships. (Konopczak & Konopczak, 2017) Cepni et al (2021 identified that both global and local factors contribute to changes in yield curves in emerging markets, limiting the transmission of monetary policy in these countries. They found that the level of yields is associated with inflation or other financial variables, while curvature is influenced by local financial factors, and slope is mostly affected by global variables.…”
Section: Bond Yields In Emerging Marketsmentioning
confidence: 99%
“…They found that the level of yields is associated with inflation or other financial variables, while curvature is influenced by local financial factors, and slope is mostly affected by global variables. (Cepni, Guney, Kucuksarac, & Hasan Yilmaz, 2021) As emphasized multiple times, the heterogeneity of emerging markets is evident in their diverse responses to external shocks. This diversity influences domestic interest rates, bond yields, and overall funding costs, as explored in the reviewed papers.…”
Section: Bond Yields In Emerging Marketsmentioning
confidence: 99%